"HIV saved My life": toward a translational model of design research through participatory design in public history and public health. Issue 1 (2nd January 2019) - Wizinsky, Matthew
Abstract: Design research and practice have multiple roles to play in articulating social and political issues related to public health. One such opportunity exists in interdisciplinary collaborations that extend beyond 'design' and 'health' disciplines and include historical methods of collection and interpretation. This article dissects the intentions and design-enabled methods behind an ongoing public history project on American women living with HIV. Participatory design methods and practical design methods have played distinct roles in the project. Maintaining a distinction between the two has helped leverage the value of both. Meanwhile, partnering participatory design with public history has generated a variety of hybrid methods for working with a marginalized community. These methods have operated to identify structural barriers to health—without eviscerating personal experiences of those barriers—in direct collaboration with participants whose medical status has a stigmatizing social impact. This case study is situated against shifting American political dynamics related to HIV/AIDS. Finally, the case study's layered approach is cast as a translational model of design research. This model is defined by the integration of basic research, applied interdisciplinary research, and community-engaged advocacy—all of which are activated through the interplay of design research and design practice.